The effect of dyeing duration and fixative on the final results of textile dyeing using purple sweet potato peel - Yunita Fitra Andriana; Mutiara Dewi Puspitawati (Institut Seni Indonesia Yogyakarta, 2022)
The fashion industry is one of the creative sectors that has significantly impacted Indonesia's economic growth. During this pandemic, the Ministry of Industry held a training program to spur the competitiveness and productivity of the textile and textile product (TPT) industry so that they can continue to run their businesses amid the pressure of the Covid-19 pandemic impact. The industries must be more innovative to be competitive in domestic and foreign markets. In this study, purple sweet potato peel was applied as a textile coloring pigment, considering its novelty and innovation value. It is expected to be an innovation in Indonesian creative industry products. So far, in the realm of textiles and fashion, purple sweet potato peel has been used as a natural textile dye, but it is less popular than other natural dyes. In addition, in Indonesia, purple sweet potato is a plant that grows throughout the year, with high quantity production and consumption rates, so that the waste of it can be used as a natural textile dye. To optimize the use of purple sweet potato peel, this study analyzes the effect of indicators on the dyeing process: the dyeing duration and the fixative used